Draft genome of the kiwifruit Actinidia chinensis - Huang, Shengxiong (Nature Pub. Group, 2013)
The kiwifruit (Actinidia chinensis) is an economically and nutritionally important fruit crop with remarkably high vitamin C content. Here we report the draft genome sequence of a heterozygous kiwifruit, assembled from ~140-fold next-generation sequencing data. The assembled genome has a total length of 616.1 Mb and contains 39,040 genes. Comparative genomic analysis reveals that the kiwifruit has undergone an ancient hexaploidization event (γ) shared by core eudicots and two more recent whole-genome duplication events. Both recent duplication events occurred after the divergence of kiwifruit from tomato and potato and have contributed to the neofunctionalization of genes involved in regulating important kiwifruit characteristics, such as fruit vitamin C, flavonoid and carotenoid metabolism. As the first sequenced species in the Ericales, the kiwifruit genome sequence provides a valuable resource not only for biological discovery and crop improvement but also for evolutionary and comparative genomics analysis, particularly in the asterid lineage.